Chapter Perspectives in Glycomics and Lectin Engineering - Tkac, Jan (Springer Nature, 2014)
This chapter would like to provide a short survey of the most promising concepts applied recently in analysis of glycoproteins based on lectins. The first part describes the most exciting analytical approaches used in the field of glycoprofiling based on integration of nanoparticles, nanowires, nanotubes, or nanochannels or using novel transducing platforms allowing to detect very low levels of glycoproteins in a label-free mode of operation. The second part describes application of recombinant lectins containing several tags applied for oriented and ordered immobilization of lectins. Besides already established concepts of glycoprofiling several novel aspects, which we think will be taken into account for future, more robust glycan analysis, are described including modified lectins, peptide lectin aptamers, and DNA aptamers with lectin-like specificity introduced by modified nucleotides. The last part of the chapter describes a novel concept of a glycocodon, which can lead to a better understanding of glycan-lectin interaction and for design of novel lectins with unknown specificities and/or better affinities toward glycan target or for rational design of peptide lectin aptamers or DNA aptamers.